Impact of routine birth early infant diagnosis on neonatal HIV treatment cascade in eThekwini district, South Africa - Vidya Kalawan; Kevindra Naidoo; Moherndran Archary (AOSIS, 2020)
Background: Early infant diagnosis (EID) of human immunodeficiency virus (HIV) and early initiation of antiretroviral therapy (ART) in HIV-infected infants can reduce the risk of mortality and improve clinical outcomes. Infant testing guidelines in KwaZulu-Natal, South Africa, changed from targeted birth EID (T-EID) only in high-risk infants to a routine birth EID (R-EID) testing strategy in 2015. Objectives: To describe the impact of the implementation of R-EID on the infant treatment cascade. Method: A retrospective analysis of a facility-based clinical database for the eThekwini district and the National Health Laboratory Services (NHLS) was conducted. All data on neonates ( 4 weeks of age) diagnosed with HIV between January 2013 and December 2017 (T-EID [2013-2015] and R-EID [2016-2017]) were extracted including follow-up until 1 year post-diagnosis. Results: A total of 503 neonates were diagnosed HIV-infected, with 468 (93.0%) initiated on ART within a median of 6 days. There was a significant increase in the estimated percentage of HIV-infected neonates diagnosed (21% vs. 86%, p 0.001) and initiated on ART (90% vs. 94.3%, p 0.001) between the T-EID and R-EID periods. Despite achieving over 90% of HIV-infected neonates diagnosed and initiated on ART in 2017, retention in care and viral suppression remained low. Conclusion: Implementation of R-EID in eThekwini district improved diagnosis and initiation of ART in HIV-infected neonates and should be recommended as part of diagnostic guidelines. These gains are, however, lost because of poor retention in care and viral suppression rates and therefore required urgent attention.